Theophylline Use to Prevent Permanent Pacing in the Contemporary Era of Heart Transplantation: The Rotterdam Experience - Kooij, Claudette; Szili-Torok, Tamas; Roest, Stefan; Constantinescu, Alina A.; Brugts, Jasper J.; Manintveld, Olivier; Caliskan, Kadir (Frontiers in Cardiovascular Medicine, 2022)
Introduction Sinus node dysfunction and atrioventricular conduction disorders occur increasingly after orthotopic heart transplantation (HTX) due to aging donors and may require permanent pacemaker (PM) implantation. Theophylline has been used in the past in selected cases as an alternative to PM implantation. Purpose The aim of this study was to investigate the rate and success of oral theophylline administration after orthotopic heart transplantation preventing permanent PM implantation. Methods We included all patients treated with theophylline post HTX due to bradyarrhythmia's in our center from January 1985 to January 2020. Data was obtained retrospectively through electronic patient files. Re-transplants and patients who died within 1 month post HTX were excluded from the analysis. Results Of the total of 751 heart transplant recipients, 73 (9,7%) patients (mean age 46 ± 15.2 years; 73% male) were treated with theophylline for bradyarrhythmia's early post HTX. Of these patients, 14 (19%) patients needed a permanent PM during hospitalization and 10(14%) patients stopped using theophylline because of adequate heart rhythm. In the end, 49 (6.5% of the total) patients were discharged with a theophylline (mean maintenance doses of 354 ± 143 mg). At the outpatient clinics, additional 6 (12%) patients needed a PM within 7 months after discharge, with the rest stable sinus rhythm. Conclusion In this retrospective data analyses oral theophylline remained a viable alternative to permanent PM implantations in patients post HTX with increased heart rates, facilitating the withdrawal of chronotropic support and avoiding the need of permanent PM implantation.